Mies - Wright en dos tensas décadas de la arquitectura moderna española - Urrutia Núñez, Ángel (Anuario del Departamento de Historia y Teoría del Arte, 1992)
Ludwig Mies van der Rohe and Frank Lloyd Wright have been two very influential architects in the world of modern architecture. Their works based on different philosophies, have represented two distinct ways of understanding the world and of conditioning the life of man. Some Spanish architects were influenced by the works of both, demonstrating with their confronting proposals, a maximum tension growing throughout the 1950’s and 60’s. Some taking Mies as a reference, with the purpose of architecture as rigorously functional, of high technology and rapid diffusion; others, taking Wright as a reference, with the purpose of offering a more organic and human alternative, but with less fortune.